A Systematic Review of Contemporary Metrics for Software Maintainability - Abílio, Ramon; Teles, Pedro; Costa, Heitor; Figueiredo, Eduardo (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2012: Anais do VI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2012)
Previous studies have been conducted with the aim of increasing the system quality. As a result, some contemporary technologies have been proposed for software development to improve maintainability, such as feature-oriented and aspect-oriented programming. Metrics are used to quantify the quality of systems developed in these technologies. Recently, contemporary metrics have been proposed or adapted from existing ones to evaluate specific issues of these contemporary technologies. This paper presents results of applying a systematic literature review to identify contemporary metrics associated with software maintainability and proposed for the feature-oriented and aspect-oriented technologies. Initially, we identify 672 published works and, after the primary selection, these quantity was reduced to 11 papers. These papers account for 33 and 78 contemporary metrics for feature-oriented and aspect-oriented technologies, respectively. The main contributions of this paper are (i) the list of metrics and measurable properties studies for feature-oriented and aspect-oriented programming, (ii) elaboration of a unified catalog of metrics applicable for both technologies, and (iii) identification of their main references.